Daya Terima dan Kandungan Gizi Soft Cookies dengan Substitusi Tepung Hati Ayam dan Tepung Daun Kelor - Islha Komariyah Maulidina; Wildan Alfira Gusrianto (Yayasan Literasi Sains Indonesia, 2026)
Anemia among adolescent girls remains a significant nutritional problem and is closely associated with inadequate intake of protein and iron. One potential strategy to address this issue is through the development of functional foods based on local ingredients. Soft cookies, as a popular snack, can be nutritionally enhanced through the substitution of chicken liver flour and moringa leaf flour, which are rich in protein and iron. This study aimed to analyze the acceptability and nutritional content of soft cookies with these substitutions. A true experimental design with a factorial Completely Randomized Design (CRD) was employed, involving two factors: chicken liver flour substitution (30%, 35%, 40%) and moringa leaf flour substitution (5% and 10%), resulting in six formulations. Acceptability was evaluated using a hedonic test by 40 untrained panelists, while nutritional analysis was conducted on the best formulation using titrimetric methods for protein and ICP-OES for iron. The results showed that substitution significantly affected color, aroma, and taste (p<0.05), but had no significant effect on texture (p>0.05). The best formulation was F3 (35% chicken liver flour and 5% moringa leaf flour), containing 14.58 g protein/100 g and 7.05 mg iron/100 g. These findings indicate that the developed soft cookies have potential as a nutritious snack alternative to support anemia prevention among adolescent girls.